(untitled) (Research, Society and Development, 2024)
The blood cycle culminates in the formation of blood components and begins with donor recruitment, screening, collection, production, serological and immunohematological analyses, storage, distribution and blood transfusion. The disposal of blood components itself can occur during each stage of this cycle and not necessarily just at the end. This will depend on the interferences that occurred in a given phase and the complications acquired during it. This study is a narrative review of the literature, of a descriptive and exploratory nature, aims to evaluate the interferences related to the disposal of blood components during the blood therapy cycle: for serological reasons, errors linked to collection and production and the underlying causes for this practice. The inclusion criteria covered the disposal of blood components due to positive serology, collection and production errors, and as an exclusion criterion, in the articles analyzed, discards for reasons linked to interruption of the transfusion at the transfusion agency and disposals due to contingency were disregarded. Among the variables for the disposal of blood components, hemolysis, difficulty in venipuncture, slow and interrupted flow, excess or insufficient volume, positive serology results, lipemia, greening of plasma, jaundice, contamination by red blood cells and expiration date stand out. The most discarded blood components in the studies analyzed were platelet concentrate (PC) and fresh frozen plasma (PFC). Considering these reasons for disposal analyzed, it is necessary to reduce them during the transfusion chain, in order to manage the stocks of blood components, so that they can be supplied for the protection and health of the recipients.